Exploring the influence of coauthorship with top scientists on researchers' affiliation, research topic, productivity, and impact. Issue 3 (August 2022) - Xie, Qing; Zhang, Xinyuan; Kim, Giyeong; Song, Min
Highlights: The study is designed to explore the influence of different proximities and types of coauthorship with top scientists on their performance. We identified the winners of four awards as top authors. The closeness and type of coauthorships between the top and ordinary scientists are identified based on the author sequence and role. The change of researcher performance considers four aspects quantitatively: affiliation, research topic, productivity, and impact. Abstract: Research studies have found that coauthorship with top scientists positively correlates with researchers' career advancement. However, the influence of different proximities and types of coauthorship with top scientists on their performance has rarely been discussed. We identified the winners of four awards as top authors. We also evaluated the effect on the researchers' affiliation change, research topic, productivity, and impact before and after three top-ordinary scientist coauthorship types (strong, moderate, and weak), examining the effect after top-top and ordinary-ordinary scientist coauthorships. Additionally, a coauthorship closeness indicator was proposed, considering the team size and author role to measure the collaboration relationship between coauthors. The results reveal that the top scientist in strong coauthorship obtained the highest affiliation change rate. For the top-ordinary coauthorship, the affiliation change rate for top scientists is higher than for ordinary scientists. For other aspects (the coauthor number, research topic, productivity, and impact), the rate after strong and moderate coauthorships increases compared to weak top-ordinary coauthorship type for top and ordinary scientists. Therefore, top scientists obtain a partner with skills, and ordinary scientists obtain more guidance. Strong and moderate coauthorships are win-win relationships for top-ordinary coauthorship types.